Back Cover: Dietary Sterols and Sterol Oxidation Products on Atherosclerosis: An Insight Provided by Liver Proteomic and Lipidomic. Issue 20 (20th October 2021) - Wang, Mengmeng; Liu, Yan; Zhao, Tian; Xiao, Fan; Yang, Xuan; Lu, Baiyi
Abstract : Mol. Nutr. Food Res . 2021, 65, 202100516 DOI: 10.1002/mnfr.202100516 Dietary phytosterols and sterol oxidation products exhibit significant different effects on atherosclerosis, and changes in liver lipid metabolism may provide another insight for their effects. As revealed by lipidomes and proteome in this report, besides cholesterol, phytosterols and sterol oxidation products also greatly affected glycerophospholipids & glycerolipids metabolism and sphingolipids metabolism. This is reported by Xuan Yang, Baiyi Lu, and co‐workers in article number 2100516 .